The Mystery of the Vanishing Benefits : An Introduction to Impact Evaluation - Ravallion, Martin (Washington, DC: World Bank, 2014)
This article provides an introduction to the concepts and methods of impact evaluation. The author provides an intuitive explanation in the context of a concrete application. The article takes the form of a short story about a fictional character's on-the-job training in evaluation. Ms. Speedy analyst is an economist in the Ministry of Finance in the fictional country of Labas. In the process of figuring out how to evaluate a human resource program targeted to the poor, Ms. Analyst learns the strengths and weaknesses of the main methods of ex post impact evaluation.